Flight Simulation Training Devices: Application, Classification, and Research - Vidakovic, Jelena; Lazarevic, Mihailo; Kvrgic, Vladimir; Vasovic Maksimovic, Ivana; Rakic, Aleksandar (International journal of aeronautical and space sciences, 2021)
Safe and efficient training using flight simulation training devices (FSTD) is one of the fundamental components of training in the commercial, military, and general aviation. When compared with the live training, the most significant benefits of ground trainers include improved safety and the reduced cost of a pilot training process. Flight simulation is a multidisciplinary subject that relies on several research disciplines which have a tendency to be investigated separately and in parallel with each other. This paper presents a comprehensive overview of the research within the FSTD domain with a motivation to highlight contributions from separate research topics from a general aspect, which is necessary as FSTD is a complex man–machine system. Application areas of FSTD usage are addressed, and the terminology used in the literature is discussed. Identification, classification, and overview of major research fields in the FSTD domain are presented. Specific characteristics of FSTD for fighter aircraft are discussed separately.